2015
DOI: 10.1007/s00248-015-0703-7
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Community Assembly in the Amazonian Dark Earth

Abstract: Here, we compare the fungal community composition and diversity in Amazonian Dark Earth (ADE) and the respective non-anthropogenic origin adjacent (ADJ) soils from four different sites in Brazilian Central Amazon using pyrosequencing of 18S ribosomal RNA (rRNA) gene. Fungal community composition in ADE soils were more similar to each other than their ADJ soils, except for only one site. Phosphorus and aluminum saturation were the main soil chemical factors contributing to ADE and ADJ fungal community dissimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 50 publications
(65 reference statements)
3
10
0
Order By: Relevance
“…3) is consistent with the decrease in fungal alpha-diversity (Chao 1 and Shannon index) with short-term additions of biochar pyrolyzed at 400°C using forest litter (Hu et al, 2014). However, in other work, no differences in fungal alpha-diversity between biocharamended soil and adjacent soils were observed (Lucheta et al, 2016). We attribute these different results to the mineralizable components of biochar.…”
Section: Fungal Taxonomic Community Affected By Biochar Propertiessupporting
confidence: 85%
See 2 more Smart Citations
“…3) is consistent with the decrease in fungal alpha-diversity (Chao 1 and Shannon index) with short-term additions of biochar pyrolyzed at 400°C using forest litter (Hu et al, 2014). However, in other work, no differences in fungal alpha-diversity between biocharamended soil and adjacent soils were observed (Lucheta et al, 2016). We attribute these different results to the mineralizable components of biochar.…”
Section: Fungal Taxonomic Community Affected By Biochar Propertiessupporting
confidence: 85%
“…An alteration of the soil fungal community composition caused by biochar additions was also found in a paddy soil (Chen et al, 2013). The fungal community composition in Amazonian Dark Earths which contain biochars from three different sites was more similar to each other than the adjacent soils without biochar (Lucheta et al, 2016).…”
Section: Fungal Taxonomic Community Affected By Biochar Propertiesmentioning
confidence: 74%
See 1 more Smart Citation
“…Biochar has special micropore structure and strong adsorption ability and can adsorb and immobilize the mineral elements necessary for plant growth in soil, and effectively regulate the cycling of nutrient elements in soil (Lehmann et al 2011, Altland and Locke 2013, Randolph et al 2017. It can effectively improve soil physical and chemical properties, reduce nutrient leaching and volatilization, and ensure adequate nutrient supply (Headlee et al 2014, Liao et al 2016, Lucheta et al 2016 and also change the structure of soil microbial community, affect the growth and activity of microorganisms, and then affect the growth of crops (Bruun et al 2014, Rehrah et al 2016, Xu et al 2016. Biochar has a strong adsorption effect on ammonium nitrate nitrogen in soil, which can slow down nitrogen leaching loss, improve soil nitrogen retention capacity and promote nitrogen uptake and utilization efficiency of crops (Zheng et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…black pigment of the fungus Aspergillus niger), whereas in ADE, it was not possible to assign a pyrogenic or a biogenic source of BC based on the distribution pattern of BPCA. In fact, Lucheta et al (2016) reported that Aspergillus niger was more abundant in ADJ than ADE. Biogenic sources of BC have been considered significant (Glaser and Knorr, 2008) or negligible (Brodowski et al, 2005b).…”
Section: Main Findings and Conclusionmentioning
confidence: 99%